(untitled) - Nguyễn, Thị Thanh Quyên (Cần Thơ, 2018)
The current study aims to answer two questions including: What are non-English majored students‟ perceptions of self-assessment in writing English paragraphs? How do the students practice self-assessment in writing English paragraphs?
Keywords: Tiếng Anh,English language; Học và dạy học,Study and teaching